2020
DOI: 10.1002/advs.201903464
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Force‐Focusing Effect in Mechanophore‐Linked Nanocomposites

Abstract: Enhanced force transmission to mechanophores is demonstrated in polymer nanocomposite materials. Spiropyran (SP) mechanophores that change color and fluorescence under mechanical stimuli are functionalized at the interface between SiO2 nanoparticles and polymers. Successful mechanical activation of SP at the interface is confirmed in both solution and solid states. Compared with SP‐linked in bulk polymers, interfacial activation induces greater conversion of SP to its colored merocyanine form and also signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 43 publications
3
38
0
Order By: Relevance
“…Furthermore, the force threshold, being dictated by scissile bond energy, is not amenable to chemical tuning and often the material has already sustained considerable permanent damage when the mechanophore activates, [ 18 ] although recent work has demonstrated that it is possible to lower the strain and stress of activation by incorporating stress‐concentrators in the material, such as voids [ 19 ] or silica nanoparticles. [ 20 ] Mechanochromic photonic materials such as colloidal photonic elastomers are inherently more tuneable and provide continuous mechano‐sensing output, yielding grayscale mechanographs. However, such materials have limited dynamic range restricted to imaging only small strains, and cannot give any insights on the mechanical processes at molecular length scales, where mechanical damage initiates.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the force threshold, being dictated by scissile bond energy, is not amenable to chemical tuning and often the material has already sustained considerable permanent damage when the mechanophore activates, [ 18 ] although recent work has demonstrated that it is possible to lower the strain and stress of activation by incorporating stress‐concentrators in the material, such as voids [ 19 ] or silica nanoparticles. [ 20 ] Mechanochromic photonic materials such as colloidal photonic elastomers are inherently more tuneable and provide continuous mechano‐sensing output, yielding grayscale mechanographs. However, such materials have limited dynamic range restricted to imaging only small strains, and cannot give any insights on the mechanical processes at molecular length scales, where mechanical damage initiates.…”
Section: Introductionmentioning
confidence: 99%
“…The fractional activation of HT-CD in the matrix is quite small, and we hypothesized that the mechanochromic response could be enhanced in two ways. First, by placing the mechanophore at the particle-matrix interface to take advantage of stress concentration effects, [21,23] and, second, by using a more mechanically labile mechanophore. [45] For the latter purpose, we targeted the head-to-head coumarin dimer (HH-CD, Figure 3a).…”
mentioning
confidence: 99%
“…What is already known is that the stress transfer within the complex composites determines the overall mechanical properties, a build-in sensitive stress probe thus would be helpful for understanding their complex mechanical behaviors. [26][27][28] Herein, with the dispersion of different surface-modified Janus nanofillers (sheets or hollow spheres) into the 1,2-dioxetane containing Semi-IPNs, a new kind of mechanochemiluminescent Semi-IPNs nanocomposites with enhanced mechanical properties and stress-reporting capability were developed. Comprehensive characterizations based on fourier transform infrared spectroscopy (FT-IR), differential scanning calorimetry (DSC), scanning electronic microscope (SEM), and tensile tests demonstrated that the hierarchically crosslinked structures, including H-bond interactions mediated by Janus nanoparticles and chemical crosslinking within Semi-IPNs, jointly contributed to excellent mechanical properties of the composites.…”
Section: Doi: 101002/marc202000442mentioning
confidence: 99%